Evaluation of Economic Supply Price of Energy Sources in Selected Regions of Nepal: Its Relevance in Rural Energy Policy Formulations - Rijal, Kamal; Bansal, N.K.; Grover, P.D. (Economic Journal of Nepal, 1990)
Not Available.